Forestry effects on a boreal ground beetle community in spring: Selective logging and clear-cutting compared - Atlegrim, Ola; Sjöberg, Kjell; Ball, John (Entomologica Fennica, 1997)
To compare the effects of two tree harvesting methods (clear-cutting and single tree selection felling), spring-occurring ground beetles (Carabidae) were studied by pitfall trapping in northern Sweden. Species abundance, total abundance and Hill’s diversity indices were used to compare the ground beetle community in clear-cuts to selectively-logged and to uncut control forests. In addition, to highlight the importance of site replication when evaluating a spatially-variable ecosystem like the boreal forest, we consider how our conclusions might have differed with and without site replication. Results from the two analyses differed considerably, highlighting the importance of site replication in studies offorestry effects in order to increase confidence in the conclusions. Overall, no significant harvest effects were found on the ground beetle community except for a significantly higher abundance of the open habitat species P. assimilis in clear-cuts than in uncut control forests. Our results thus do not support suggestions of an increase in diversity following clear-cutting, but are consistent with previous findings regarding increased abundances of open habitat species and no changes in abundance of forest generalists in clear-cuts. In general, the carabid community in the selection loggings resembled that in the uncut control forest, indicating a low effect of this harvesting method. Based on our analysis, we suggest that future studies of forestry impacts on invertebrates attempt to increase the number of sites evaluated rather than increase the number of samples from a given area.